The Mitford vanishing - Fellowes, Jessica (The Mitford murders, 2022)
"A mystery with the fascinating Mitford sisters at its heart, Jessica Fellowes's The Mitford Vanishing is the fifth installment in the Mitford Murders series, inspired by a real-life murder in a story full of intrigue... "Downton Abbey meets Agatha Christie in this witty and twisty mystery." -In Touch Weekly on The Mitford Murders 1937. War with Germany is dawning, and a civil war already rages in Spain. Split across political lines, the six Mitford sisters are more divided than ever. Meanwhile their former maid Louisa Cannon is now a private detective, working with her policeman husband Guy Sullivan. Louisa and Guy are surprised when a call comes in from novelist Nancy Mitford requesting that they look into the disappearance of her Communist sister Jessica in Spain. But one case leads to another as they are also asked to investigate the mysterious vanishing of a soldier. As the two cases come together, Louisa and Guy discover that every marriage has its secrets-but some are more deadly than others. Suddenly home feels a long way away.."--